Catálogo de las bibliotecas escolásticas barcelonesas en los siglos xiii y xiv - Sara Gonzalez (Atalaya)
This article aims to rebuild the catalogues of the Barcelona scholastic libraries (those of the Dominicans, the Franciscans and the Discalced Carmelites) by the end of the Middle Ages. The inventories are based on the few remaining manuscripts of that time and on some research works about conventual libraries. The account of the formerly mentioned libraries is completed by a thematic presentation of their manuscripts.